17 The presentation, management and outcomes of truncus arteriosus in south wales, 1967–2015. (2nd February 2018) - Ferguson, T; Pateman, A
Abstract : Purpose: Truncus arteriosus is a rare congenital heart defect consisting of a single artery arising from both ventricles and a ventricular septal defect. Survival beyond the first year of life is very rare if the truncal defect is not treated. Currently, no research reports on this patient group in South Wales. The aim of this work was to evaluate the presentation, management and outcomes of truncus arteriosus in South Wales and compare this to outcomes published by other UK centres. Methods: Data were collected retrospectively for the period January 1967 to December 2015. All patients on the database with a diagnosis of truncus arteriosus were used (n=47). Results: Overall survival was 70% in patients followed-up for 13.9 years (0.8–30.7). Treated survival was 81% in patients followed-up for 12.3 years (0.8–30.7). Overall freedom from reintervention was 9% with conduit replacement being the most common reoperation (28/34 patients) after an average of 4.4 years (0.3–16.3). Xenograft use and antenatal diagnosis were associated with a significantly shorter interval to conduit replacement. The prevalence of DiGeorge syndrome in this study was 21% which was associated with developmental delay or learning difficulties but not with poorer cardiac outcomes. Conclusion: Truncus arteriosus repair can be achieved with good outcomes in terms of long term survival but freedom from reintervention is low. Prolonging conduit lifespan remains the major challenge in managing these patients.